An Approach in Pursuance of Differentiation Inducers to Combat Cancer via Targeting of Abnormal Methylation Enzymes - Liau, Ming C.; Kim, Jai-Hyun; Fruehauf, John P. (Highlights on Medicine and Medical Research Vol. 2, 2021)
Cell differentiation agent-2(CDA-2) was a preparation of urinary differentiation inducers (DIs) and differentiation helper inducers (DHIs), which was a promising hypomethylating agent approved by the Chinese FDA for the therapy of myelodysplastic syndrome (MDS). DIs are chemicals capable of eliminating telomerase from abnormal MEs commonly found in human cancers. The major DI of CDA-2 is an organic acid without UV absorption. Without UV absorption as a guide, it was difficult to purify the DI of CDA-2 for identification. Thus, we pursued possible candidates to function as DIs in this study. Cancer MEs become abnormal due to association with telomerase. Naturally we sought telomerase inhibitors as possible candidates of DIs. Prostaglandin E2 (PGE2) attracted our attention because it was implicated to involve in wound healing, which is a major biological mission of progenitor stem cells (PSCs) and cancer stem cells (CSCs). Eradication of CSCs has been a major focus of our studies. Besides, PGE2 fits the description of the major DI of CDA-2. Induction of terminal differentiation (TD) of HL-60 cells by NBT assay was employed to evaluate the activity of chemicals as DIs. Cell growth was based on cell numbers. All-trans retinoic acid (ATRA) and 12-O-tetradecanoylphorbol-13-acetate (TPA) are two well known DIs. ATRA displayed a wide active dosage range from 0.2 to 4.5 µM with a maximum of inducing 89% NBT+ cells at 3 µM. TPA displayed a narrow active dosage range from 0.2 to 0.6 nM with a maximum of inducing 84% NBT+ cells at 0.4 nM. BIBR1532 and bodine were the two telomerase inhibitors studied. Both were found active as DIs. BIBR1532 was active in the dosage range from 30 to 75 µM with a maximum of inducing 86% at 63 µM. Bodine was active in the dosage range from 60 to 98 µM with a maximum of inducing 80% at 98 µM. PGE2 was active in the dosage range from 20 to 70 µM with a maximum of inducing 80% at 56 µM. 16, 16-dimethyl PGE2 has the potential as an acceptable DI, which has been shown to display effective inhibitory activity against spontaneous evolution of cancer. DIs at dosages not active as DIs could function as effective DHIs to other DIs. RIsub0.5 of BIBR1532, boldine and PGE2 as DHIs were 2.02 µM, 3.11 µM, and 0.92 µM, respectively. DIs alone, no matter how effective, could not induce NBT+ cells to reach 100%. 95% (89% plus 6% of blank) was the highest value achieved by ATRA. Incomplete induction of TD was the reason for frequent recurrence when ATRA was used alone in the therapy of acute promyelocytic leukemia (APL). A combination of ATRA and a DHI could induce NBT+ cells to reach 100% to avoid recurrence.